Transcriptomic Analyses and Potential Therapeutic Targets of Pancreatic Cancer With Concomitant Diabetes - Xu, Tingting; Xu, Xiaoxuan; Liu, Peng-Cheng; Mao, Hui; Ju, Shenghong (Frontiers in Oncology, 2020)
Background Type 2 diabetes mellitus (T2DM) known as non-insulin-dependent diabetes mellitus, which is increasingly acknowledged as being associated with an increased risk for a series of cancers. Pancreatic cancer is currently the fourth most common cause of cancer-related mortality, which has been proved to be worsened by internal diabetic condition. However, the underlying molecular mechanisms are less addressed. Furthermore, current knowledge revealed that therapeutic strategy by anti-diabetes for pancreatic cancer under diabetes condition have no satisfactory efficacy, and nor by chemotherapy in our study. Methods To clarify these mysteries and widen our knowledge, both obesity-associated and non-obese-associated T2DM mouse models were generated by chemical induction with streptozotocin (STZ) and leptin receptor knockout (db/db) in mice. Then, the process of tumour progression was researched, and the gene expression profiling of pancreatic cancer in mice was performed using RNA-seq. Results Our results showed that pancreatic cancer malignancy was increased with notable proliferation and metastatic potential in two diabetic mice model. Totally, 136 and 64 significantly differentially expressed genes (DEGs) were identified in STZ and db/db mice by transcriptomic analysis. The results also suggested that different carcinogenesis-related genes and potential molecular mechanisms contribute to the malignancy of pancreatic cancer in obesity-associated and non-obesity-associated T2DM. In obesity-associated db/db mice, the GO subcategories associated with most of the genes with downregulated expression are involved in the immune response. However, in non-obesity-associated STZ mice, in addition to the immune response category, the enriched subcategories also included angiogenesis and the extracellular matrix. While, two genes respectively encoding MMP-2 and MMP-9 were simultaneously abnormal up-regulated in pancreatic cancer tissue from diabetic mice of both STZ and db/db, that could act as potential therapeutic targets for significantly suppressing the malignant progression. Furthermore, an optimizing therapeutic strategy was further proposed that combining MMP-2/9 inhibitor with gemcitabine significantly enhanced anti-tumour effects on pancreatic cancer under diabetic condition, providing a theoretical basis for clinical applications. Conclusions Generally, this study provides a comprehensive insight into diabetes as a risk factor for pancreatic cancer and has the potential to guide the development of enhanced treatment strategies.